The interrelationship between migration and crime (Journal of actual problems of jurisprudence, 2018)
The transformation of social relations in the context of globalization, along with the positive has its negative consequences of the criminalization of relations, changing crime patterns, modification of known and new types of crime. The article explores the relationship between migration and specific set of crimes committed by migrants in Kazakhstan combined common criminal sphere and interests. Model is a problematic situation in the field of criminal attacks on public relations in the sphere of security of life of citizens; public safety and public order, the public authorities; peace and security of mankind.Key words: migration, migrant, migration crime, illegal migration, crime, migration crime.